Identifying the factors that affect the oral participation among EFL Libyan understudy learners at the Department of English, Sirte University. - Nouriya Muftah Elsaadi; Mariam Aqila (مجلة جامعة سرت للعلوم الانسانية, 2023)
This study aims to identify the possible factors that might cause the oral participation problems among EFL Libyan understudy learners at the Department of English, Sirte University. Thus, a quantitative design was employed in this study using a close-ended questionnaire in order to obtain the required data. The data was analyzed manually. In the study, 25 students were selected non-randomly to complete the questionnaire. The results indicated that there are some factors which influence the learners’ oral participation such as fear of mistake and criticizing, shyness, lack of confidence, lack of vocabulary, inability to express their ideas and thoughts, lack of motivation, lack of support, lack of time. These factors are involved into four groups: students’ factors, teachers’ factors, curriculum’s factors and environments’ factors. The researchers adopted some recommendations that will be useful for teachers as well as learners.